Transcriptional analysis of interspersed repetitive polymerase III transcription units in human DNA. - Elder, J T (1981)
The template for RNA polymerase III in vitro transcription found on the human DNA clone pJP53 was shown in the previous paper to enclose a member of the Alu famiy of interspersed repetitive DNA sequences. We have mapped this transcript onto its template in greater detail by comparison of the template DNA sequence to the base composition of the Tl ribonuclease digestion products of the in vitro transcript. We find that the 5' end of the transcript lies in close proximity to the 5' end of the conserved Alu family sequence as analyzed in the preceding paper. The 3' end of the transcript appears to terminate in a U-rich region beyond the region of Alu family sequence conservation. Analysis of cellular RNA by Northern blotting and hybridization with a DNA probe derived from another Alu family transcription template demonstrates abundant representation of sequences homologous to the reiterated DNA. Cytoplasmic, nonpolyadenylated RNA from human and murine cells contains a monodisperse, 300 nucleotide species, recently determined by Weiner (4) to be the 7S RNA. In contrast, the Alu-homologous transcripts are heterodisperse in mRNA and hnRNA, with the highest specific representation of Alu family sequences being found in oligo(dT)-retained hnRNA.